(untitled) (International Journal of Engineering and Computer Science, 2013)
In Wireless Sensor Networks (WSNs)data transfer is achieved through the intermediate nodes by hopping, while minimising the hop count, the utilisation of energy and time latency of an individual node are minimised. The main idea behind this paper involves data accuracy in collection of data from a sensor node to the Base Station (BS) and to reduce the energy consumption which will proportionally increase the speed. The technology in Data Gathering (DG) composes distribution of sensor nodes in an environment, Mobile Sink (MS) for collecting data from a Cluster Head (CH) among the nodes. The data from a distant sensor node reaches the CH via relay nodes then transmits to MS and to BS. The main issues behind this technology is, from which node the data is acquired is not known by BS, time latency in aggregation of data and energy consumption of node due to relaying of data. In order to overcome such issues, a new concept in networking called Localisation is implemented, where the position information about the sensor node is gathered by the BS with the help of Beacon nodes, which helps to improve efficiency in collection of data, reduces time latency and energy consumption of a sensor node, in addition a polling scheme is implemented to reduce the relaying of data from the sensor nodes. A value added scheme to minimize the error in acquired data from a sensor node to CH and to eliminate buffering problems Cache optimization is implemented in proposed work